The finger feeding method and relactation - Karabayır, Nalan; Merttürk Potak, Edanur; Karaman, Sümeyye; Sebirli, Muhammed Fatih; İstanbullu, Mustafa Beykan; Potak, Mehmet; Teber, Burcu Gizem (Cureus Inc., 2022)
Background: Breastfeeding is one of the most important factors ensuring the healthy growth and development of babies. Preterm babies, babies with metabolic, neurological, or developmental delays, babies separated from their mothers for any reason, and adopted babies need alternative feeding methods. This study was carried out to investigate the effect of the finger feeding (FF) method on relactation. Method: In this retrospective study, infants who were admitted to the Istanbul Medipol University breastfeeding counseling clinic between January 2020 and June 2021 and were recommended to be fed with finger feeding were evaluated. Gender, gestation, mode of delivery, birth weight, age, cause for admission, feeding type, breastfeeding starting time, finger feeding time, and breastfeeding duration of the cases were recorded from the counseling forms. Results: Of 41 babies, 29.3% were girls and 70.7% were boys, and 82.9% were term. Seventeen (41.5%) were horn with spontaneous vaginal delivery and 24 (58.5%) with a cesarean section. The most common reason for admission was found to be the inability to latch. While 30 (73.2%) of the babies fed with finger feeding were able to suck, nine babies continued to be fed with a bottle, one baby with a spoon, and one baby with a supplemental nursing system (SNS). The breastfeeding starting time was 23.1 +/- 27.5 (1-100) days. Conclusion: The finger feeding method is an effective alternative feeding method for successful breastfeeding. There is a need for studies to be conducted with more babies, both preterm and term, in this regard.
Keywords: Induced Lactation; Relactation; Bottle Feeding; Supplementary Nursing System; Finger-Feeding; Breastfeeding